The Use of Nano Influencers on Social Media to Enhance Public Knowledge in the Indonesian Cultural Institution Program - Manggala Putra (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study examines the use of nano influencers on social media to increase public awareness of cultural institution programs in Indonesia. Nano influencers, who have between 500 and 10,000 followers, are considered effective in building audience engagement through a personal and authentic approach. Institutions such as Balai Media Kebudayaan (BMK) which manages the digital platform IndonesianaTV, utilize nano influencers to disseminate cultural information widely but still relevant to certain audiences. The purpose of this study is to explore how collaboration between cultural institutions and nano influencers can increase public awareness and understanding of local culture. The research method used is descriptive qualitative with an inductive approach, where data was collected through interviews and observations of 20 nano influencer accounts that are active in promoting IndonesianaTV. The results of the study show that educational content delivered by nano influencers on social media has succeeded in reaching small but significant communities, as well as building positive public perceptions of local culture. These findings can be a reference for other cultural institutions in utilizing digital communication strategies to get closer to their audiences and increase their interest in Indonesian culture.